PELATIHAN BERFIKIR POSITIF UNTUK MENANGANI SIKAP PESIMIS DAN GANGGUAN DEPRESI Positive Thinking Training as a Treatment for Pessimistic Attitude and Depression - Lestari, Anita (Faculty of Psychology, Universitas Gadjah Mada, 1997)
According to the cognitive theory, pessimistic attitude and depression are caused by negative thoughts, that is, a negative concept of the future, the self, and the outer world. A person who is depresed and has a pessimistic attitude, interprets any event in a negative way, focuses on negative aspects of any situation, and also has hopeless expectation about the future. He/she also has a pessimistic explanatory style, seeing the causes of bad events as permanent, universal and internal, and the causes of good events as temporary; specific and external.